The Influence of Mobile Legends: Bang Bang Playing Intensity on Community Religiosity in Indrapuri District - Ilham Mushawwir (Muqaranah Al-Adyan: Multidisciplinary Perspective on Religions, 2026)
This study aims to analyze the influence of the intensity of playing the online game Mobile Legends: Bang Bang on the religiosity of people in Indrapuri District, Aceh Besar Regency. The rapid development of digital technology has made online gaming one of the most popular forms of entertainment across various social groups. On the one hand, online games provide several benefits, including the enhancement of strategic thinking, teamwork, communication skills, and social interaction. On the other hand, excessive gaming intensity may affect individuals’ religious lives, particularly in terms of worship practices and the internalization of religious values. This research employed a descriptive qualitative approach. Data were collected through observation, semi-structured interviews, and documentation. Informants were selected using purposive sampling and included active Mobile Legends players, parents, religious leaders, and community leaders. Data were analyzed through the stages of data condensation, data display, and conclusion drawing and verification. The findings reveal that Mobile Legends playing behavior encompasses teamwork, competitiveness, strategic thinking, social interaction, supportive attitudes, as well as negative behaviors such as toxic communication and addictive tendencies. The game contributes positively to the development of cognitive abilities, communication skills, teamwork, and recreational well-being. However, excessive gaming intensity may lead to physical health problems, sleep disturbances, weakened social relationships, and reduced participation in religious activities. Furthermore, the use of inappropriate language and aggressive behavior within the game environment may conflict with religious values that emphasize politeness, self-control, and respect for others. The study concludes that there is a significant influence of Mobile Legends: Bang Bang playing intensity on the religiosity of the community in Indrapuri District. Therefore, effective time management and proportional use of online games are necessary to ensure that the benefits of gaming do not diminish individuals’ religious commitment and spiritual well-being